Intestinal microbiome analyses identify melanoma patients at risk for checkpoint-blockade-induced colitis - Dubin, Krista; Callahan, Margaret K.; Ren, Boyu; Khanin, Raya; Viale, Agnes; Ling, Lilan; No, Daniel; Gobourne, Asia; Littmann, Eric; Huttenhower, Curtis; Pamer, Eric G.; Wolchok, Jedd D. (Nature communications, 2016)
The composition of the intestinal microbiota influences the development of inflammatory disorders. However, associating inflammatory diseases with specific microbial members of the microbiota is challenging, because clinically detectable inflammation and its treatment can alter the microbiota’s composition. Immunologic checkpoint blockade with ipilimumab, a monoclonal antibody that blocks cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) signalling, is associated with new-onset, immune-mediated colitis. Here we conduct a prospective study of patients with metastatic melanoma undergoing ipilimumab treatment and correlate the pre-inflammation faecal microbiota and microbiome composition with subsequent colitis development. We demonstrate that increased representation of bacteria belonging to the Bacteroidetes phylum is correlated with resistance to the development of checkpoint-blockade-induced colitis. Furthermore, a paucity of genetic pathways involved in polyamine transport and B vitamin biosynthesis is associated with an increased risk of colitis. Identification of these biomarkers may enable interventions to reduce the risk of inflammatory complications following cancer immunotherapy. A subset of cancer patients treated with immune checkpoint blockade develops colitis. Here the authors show that lower abundance of Bacteroidetes and vitamin B biosynthetic modules in fecal samples of melanoma patients can predict their susceptibility to colitis following anti-CTLA-4 treatment.